1996
DOI: 10.1016/0014-5793(96)00328-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the heptameric pore‐forming complex of the Aeromonas toxin aerolysin using MALDI‐TOF mass spectrometry

Abstract: Aerolysin, a virulence factor secreted by Aeromonas hydrophila, is representative of a group of ~-sheet toxins that must form stable homooligomers in order to be able to insert into biological membranes and generate channels. Electron microscopy and image analysis of two-dimensional membrane crystals had previously revealed a structure with 7-fold symmetry suggesting that aerolysin forms heptameric oligomers [Wilmsen et al. (1992) EMBO J. 11, 2457-24631. However, this unusual molecularity of the channel remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 36 publications
1
65
0
3
Order By: Relevance
“…Except in cases where the association constant is extremely high [30], MALDI mass spectrometry is not suitable for observation of noncovalently bound species. In order to observe the oligomeric forms of HSP90, EDC was used to cross-link interacting species prior to MALDI mass spectrometric analysis.…”
Section: Mass Spectrometry Of Oligomeric Speciesmentioning
confidence: 99%
“…Except in cases where the association constant is extremely high [30], MALDI mass spectrometry is not suitable for observation of noncovalently bound species. In order to observe the oligomeric forms of HSP90, EDC was used to cross-link interacting species prior to MALDI mass spectrometric analysis.…”
Section: Mass Spectrometry Of Oligomeric Speciesmentioning
confidence: 99%
“…Interestingly, we could not detect any gaseous noncovalent inhibitor-protease ions at these conditions, presumably due to the lower highmass sensitivity of MCP detectors. Several major effects have been described to result in nonnative conditions for the noncovalent complexes: MALDI matrix [3][4][5], sample preparation [4,6,7], crystal morphology [4,8,9], pH of the solution [6, 10 -12], organic solvent [7,8], ionic strength [13,14], matrix/analyte ratio [15,16], speed of solvent evaporation [4], and sample concentration [9,15]. The effect of some instrumental parameters in the detection of complexes has also been studied; extraction delay time, positive/negative ion mode, linear/reflector and acceleration mode were found to be of minor importance [7,17], whereas laser pulse energy [8,17,18] and the number of laser shots (i.e., "first shot phenomenon") [4,8,13,19,20] was reported to be a decisive factor in a number of cases.…”
mentioning
confidence: 99%
“…This work showed the feasibility of directly measuring hydrogen/deuterium exchange kinetics of detergent-solubilized proteins in solution by ES mass spectrometry and thereby obtaining structural information. Although ES has now been extensively used in the direct study of noncovalent interactions, the application of matrix-assisted laser desorption ionization (MALDI) in this area of research been more restricted, although it should be noted that Van Dorsselaer et al (33,34) have reported MALDI data on the subunit stoichiometry of high mass noncovalent complexes of membrane proteins.…”
mentioning
confidence: 99%